Foreign workers in Spain: Inflexibility of the legal status? against market flexibility? (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
This study examines the misalignment, despite successive reforms of immigration laws in Spain, of the legal framework concerning labour relations for those who work for others with the legal statute on immigrants, thereby failing to meet the integratingaim in which work represents the primary inclusion factor. The authors analyse the most important aspects of this lack of coordination, such as the quota of foreign workers, initial residency and work permits for those who work for others and therenewal conditions thereof.
Keywords: Immigration; foreign workers; social inclusion